Autotetraploid Coffea canephora and Auto-Alloctaploid Coffea arabica From In Vitro Chromosome Set Doubling: New Germplasms for Coffea - Venial, Lucimara Ribeiro; Mendonça, Maria Andréia Corrêa; Amaral-Silva, Paulo Marcos; Canal, Guilherme Bravim; Passos, Ana Beatriz Rocha de Jesus; Ferreira, Adésio; Soares, Taís Cristina Bastos; Clarindo, Wellington Ronildo (Frontiers in Plant Science, 2020)
Polyploidy is more than two chromosomal sets per nucleus, as the allotetraploid Coffea arabica. Due to allotetraploidy, C. arabica shows different phenotypes compare to diploid Coffea species, highlighting by beverage quality produced from its grains. Looking for the possibility of new phenotypes coupled with economic feature, considerable progress since 60’s was reached for synthetic chromosome set doubling (CSD) in vitro, involving especially the antitubulin compounds, biological material, and used tissue culture pathway as the indirect somatic embryogenesis (ISE). Here, we aimed to regenerate autotetraploid and auto-alloctaploid plantlets of Coffea canephora and C. arabica, respectively, from a novel in vitro CSD procedure for Coffea. Exploring the ISE pathway, we treated the cellular aggregate suspensions (CAS) with 0.0 (control), 0.5, 1.5, or 2.5 mM of colchicine solution for 48, 72, or 96 h and maintained in liquid medium under constant orbital shaking. After transferring the CAS to semisolid media for somatic embryo regeneration, we considered it as cellular mass. Mature cotyledonary somatic embryos were only regenerated from cellular masses treated with 2.5 mM/48 h and 2.5 mM/72 h for C. canephora and with 0.5 mM/48 h for C. arabica. Evaluating the DNA ploidy level and the chromosome counting revealed that 36 (34.9%) plantlets of C. canephora were autotetraploids (4C = 2.86 pg, 2n = 4x = 44) and 61 (21.1%) of C. arabica were auto-alloctaploids (4C = 5.24 pg, 2n = 8x = 88). The CSD procedure, exploring the CAS proliferation and ISE pathway, promoted whole-genome duplication and resulted in a relatively high number of solid polyploids of both Coffea species. Due to distinct responses, DNA sequence fidelity (genetic) and global level of 5-methylcytosine (epigenetic) were evaluated. We observed that the increase of 5-methylcytosine levels was associated with somatic embryo regeneration from cells showing DNA sequence fidelity for the tested SSR primers. In conclusion, the adopted procedure for in vitro CSD is reproducible for induction, regeneration and propagation of Coffea polyploids and potentially other shrubbery and woody species. In view of the novelty of this procedure to generate new germplasm, we show the key issues and the steps of the CSD procedure.